POLA RUANG DALAM LANSEKAP PEDESAAN: PENILAIAN PERUBAHAN GUNA LAHAN DAN TUTUPAN VEGETASI - Iwan Rudiarto; Wiwandari Handayani; Holi Bina Wijaya; Pangi Pangi (Diponegoro University, 2017)
The existence of rural landscape is very significant in balancing the biohysical environment. The changing of landscape pattern in a rural area affects both the ecosystem and the habitat where eventually changes the human environment. Normaliazed Difference Vegetation Index/NDVI is one of the assessment that can be applied in determining the distribution of vegetation coverage. The analysis was carried out through the assessment of landsat satellite images in the year of 1990, 2010, and 2015 in three typical rural areas; coastal area, plain area, and mountain area. The result showed that coastal rural and plain rural area were the two areas that vegetation coverage significantly changed. This change is mostly found in the intermittent vegetation classification which identified as the agricultural and settlement area. While in the mountain area, the conversion was identified more on the agricultural area due to the expansion of agricultural activity to the higher area.